The endorsement Selebgram Abang Lapar to Buying Interest of Consumers: evidence from Palangka Raya - Agustin, Lestia Rahmah; Arifin, Muhammad Zainal; Wehdawati, Wehdawati; Malisi, Muhammad Ali Sibram; Sadikin, Ali (AL-QARDH, 2023)
Marketing from businesses or businesspersons uses social media influencers to enhance consumer interest and sales, as well as contribute to brand awareness. Given the increasingly fierce economic rivalry in Palangka Raya, it is difficult for business owners to survive and grow their businesses. This research's objective was to examine and determine the impact of the Abang. Lapar program's endorsement on the purchasing intentions of Palangka Raya customers. This type of research is expost facto. This research employed a statistical associative approach. Methods for collecting data via questionnaires and written documents. This research's population consisted of 15,600 followers of the Instagram account Abang.Lapar, the sample consisted of 100 participants whose values were estimated using the Slovin formula with a 10% margin of error. Using IBM SPSS Statistics 22, a simple linear regression analysis, correlation test, t test, and coefficient of determination (R2) test are utilized to analyze the data. The results of a simple linear regression analysis indicate a significant value of 0.000 <0.05, indicating a significant influence. The result of the test obtained a Pearson correlation value of 0.756, which indicates that the degree of association is substantial. The conclusion is therefore that H0 is rejected and H1 is accepted. The result of the coefficient of determination (R Square) is 0.572, which indicates that the independent variable (endorsement) can explain 57.2% of the Palangka Raya consumers' buying interest, while the remaining 42.8% is explained by other variables. Therefore, 57.2% is classified as having a moderate impact. Thus, it can be argued that Abang.Lapar's endorsement of Palangka Raya has increased consumer interest in the product.